ECCB's operational framework and capital market development conflict or synergy? - Nicholls, Garth ([s.n.[Caribbean Centre for Money & Finance] [st. Augustine]TT, 1995)
Discusses the Eastern Caribbean Central Bank's experience in implementing monetary policy and its plans for the future. Highlights the advantages of the ECCB's operational framework for macroeconomic adjustment and the management policy.